Distribution of family farms according to estate size and land usage in Hajdú-Bihar County - Nagyné Demeter, Dóra (Acta Agraria Debreceniensis, 2007)
In harmony with European tendencies, the role of agriculture and its share in GDP output, as well as in employment, is continuously decreasing in Hungary and Hajdú-Bihar County. At the same time, according to the specialized literature, the role of agriculture is still extremely important in the income of the rural population and in easing the present social tensions, and this will not change in the future. The economic and social processes of the last one and a half decades caused radical changes in agriculture. The above-mentioned processes resulted in new property and organizational structure in the field of leasehold and land structure. The rational land concentration which came to pass in the last few years can be mentioned as a favourable tendency that improves the efficiency of agricultural activities, as well as the more effective land usage accompanied by this process. In addition, it supports the integration with principles formulated in the Common Agricultural Policy. In this study, I survey the effects of established processes and the change of land usage in the case of individual family enterprises in Hajdú-Bihar County. The choice of the examination area was motivated by the higher proportion of agricultural area in comparison with the national average and the fact that this sector has great importance today, too.